PERAN ORGANISASI SANTRI DALAM MEMBENTUK KEDISIPLINAN PESERTA DIDIK DI LINGKUNGAN PESANTREN IDRISIYYAH - Syifa Al Nizar, Muhammad; Wisa Belinda, Ulfi; Sriwahyuni, Emi (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study aims to analyze the contribution of student organizations in shaping student discipline at Idrisiyyah Islamic Boarding School. It addresses a gap in previous studies that have not thoroughly examined the role of student organizations as agents of discipline in daily pesantren practices. These organizations function as platforms for character development, reinforcement of responsibility, and supervision of rule compliance. This research uses a descriptive qualitative approach with the Miles & Huberman model, employing questionnaires, observations, and interviews for data collection. The findings indicate that student organizations play a significant role in fostering discipline, particularly in religious practices, adherence to rules, environmental cleanliness, and participation in academic activities. A total of 87% of respondents stated that involvement in OSPI helped them become more organized and value time, while 80% joined to develop responsibility and serve as role models. This involvement contributes to personal character building, strengthens a sense of responsibility, and fosters consistency in fulfilling duties. Supporting factors include collaboration among organizational boards, guidance from mentors, structured regulations, and continuous role modeling. The main challenge is the lack of awareness among some students about the importance of discipline. These findings affirm that optimizing the role of student organizations contributes to a conducive, orderly, and sustainable educational environment. ABSTRAK Penelitian ini bertujuan menganalisis kontribusi organisasi santri dalam membentuk kedisiplinan peserta didik di Pondok Pesantren Idrisiyyah. Penelitian ini mengisi kekosongan kajian terdahulu yang belum mengkaji secara mendalam peran organisasi santri sebagai agen pembentuk disiplin dalam praktik keseharian pesantren. Organisasi santri berfungsi sebagai sarana pengembangan karakter, penguatan tanggung jawab, dan pengawasan terhadap kepatuhan aturan pesantren. Pendekatan yang digunakan adalah kualitatif deskriptif dengan model Miles & Huberman, melalui kuesioner, observasi, dan wawancara. Hasil penelitian menunjukkan organisasi santri memiliki peran signifikan dalam membentuk disiplin santri, terutama terkait pelaksanaan ibadah, kepatuhan tata tertib, kebersihan lingkungan, dan partisipasi dalam kegiatan belajar. Sebanyak 87% responden menyatakan keterlibatan dalam OSPI membantu mereka menjadi lebih teratur dan menghargai waktu, sementara 80% termotivasi bergabung untuk melatih tanggung jawab dan menjadi teladan. Keterlibatan ini turut membentuk karakter, memperkuat rasa tanggung jawab, serta membangun konsistensi dalam menjalankan kewajiban. Faktor pendukung keberhasilan meliputi kolaborasi pengurus, dukungan pembina, aturan yang terstruktur, dan keteladanan berkelanjutan. Tantangan utama adalah kurangnya kesadaran sebagian santri terhadap pentingnya disiplin. Temuan ini menegaskan bahwa optimalisasi peran organisasi santri berkontribusi dalam menciptakan lingkungan pendidikan yang kondusif, teratur, dan berkelanjutan.